To identify the pair of equivalent expressions, let's simplify each option:
-
\(2x + 2\) and \(2(x + 2)\):
- \(2(x + 2) = 2x + 4\)
- These expressions are not equivalent.
-
\(3x + 2x\) and \(x^2(3 + 2)\):
- \(3x + 2x = 5x\)
- \(x^2(3 + 2) = x^2 \cdot 5 = 5x^2\)
- These expressions are not equivalent.
-
\(2(x + 3)\) and \(2x + 6\):
- \(2(x + 3) = 2x + 6\)
- These expressions are equivalent.
-
\(-3(x + 2)\) and \(-3x - 3\):
- \(-3(x + 2) = -3x - 6\)
- These expressions are not equivalent.
The only pair of equivalent expressions is \(2(x + 3)\) and \(2x + 6\).